Do 'flexicurity' Policies Work for People With Low Education and Health Problems? A Comparison of Labour Market Policies and Employment Rates in Denmark, The Netherlands, Sweden, and the United Kingdom 1990-2010 - McAllister, Ashley; Nylén, Lotta; Backhans, Mona; Boye, Katarina; Thielen, Karsten; Whitehead, Margaret; Burström, Bo (International journal of health services, 2015)
People with limiting longstanding illness and low education may experience problems in the labor market. Reduced employment protection that maintains economic security for the individual, known as "flexicurity," has been proposed as a way to increase overall employment. We compared the development of labor market policies and employment rates from 1990 to 2010 in Denmark and the Netherlands (representing flexicurity), the United Kingdom, and Sweden. Employment rates in all countries were much lower in the target group than for other groups over the study period. However, "flexicurity" as practiced in Denmark, far from being a "magic bullet," appeared to fail low-educated people with longstanding illness in particular. The Swedish policy, on the other hand, with higher employment protection and higher economic security, particularly earlier in the study period, led to higher employment rates in this group. Findings also revealed that economic security policies in all countries were eroding and shifting toward individual responsibility. Finally, results showed that active labor market policies need to be subcategorized to better understand which types are best suited for the target group. Increasing employment among the target group could reduce adverse health consequences and contribute to decreasing inequalities in health.